Male Mammary Myofibroblastoma - Jordan Wordekemper; Reed Pierce; Timothy Christopher (Annals of Internal Medicine: Clinical Cases)
Mammary myofibroblastoma is a rare mesenchymal neoplasm that represents less than 1% of breast tumors. It is a benign lesion first described in 1987 and to date has a minimal number of reported cases. Clinical knowledge of its presence is important as it can strongly resemble malignant tumors owing to its nonspecific imaging findings and morphologically similar appearance to its aggressive counterparts. We present a case of a unilateral myofibroblastoma in a late 50-year-old male. The rare tumor was found incidentally during a cardiac work-up, which led to extensive imaging and immunohistochemical analysis to definitively make the diagnosis.